PREDICTORS OF PULMONARY TUBERCULOSIS CO-INFECTION AMONG HIV PATIENTS IN KHZ MUSTHAFA HOSPITAL: A CROS-SECTIONAL STUDY - Novianti, Siti; Lestari, Dania Puji; Lina, Nur; Sutha, Diah Wijayanti (Universitas Aisyah Pringsewu, 2025)
HIV infection increases the burden of pulmonary TB, especially in populations with a high prevalence of pulmonary TB, including in Indonesia. People with HIV infection become susceptible to other infections, including pulmonary TB. This study aims to analyze the determinants associated with the occurrence of pulmonary TB co-infection among HIV-positive patients. The study design used a crossectional study based on patient medical records, conducted on all HIV-positive patients at KHZ Mushtafa Regional Hospital, Tasikmalaya Regency, from 2022-2023 and obtained 140 respondents. Research subjects with incomplete medical records were excluded from the study. Demographic and clinical data were analyzed using SPSS to process univariate, bivariate data, and multiple logistic regression at a 95% confidence interval. A total of 59.2% of HIV patients suffered from pulmonary TB co-infection. The average age of patients was 30.7 years; 77.8% were male; 75.9% were married; and 69.3% were employed. Multivariate analysis results showed that clinical stage (p=0.009; OR 2.9 (1,319-6,734), duration of ARV therapy (p0.001, OR=5.3 (2,246-12,474), and the presence of other opportunistic infections (p0.001, OR=4.6 (1,963-11,005)) were the significant predictors of TB/HIV co-infection at KHZ Musthafa Regional Hospital, Tasikmalaya Regency. The high prevalence of pulmonary TB indicates low screening in at-risk population groups. Integrated and comprehensive services for pulmonary TB and HIV diagnosis and treatment are needed for better management of TB/HIV co-infection.